Adherence to COVID‐19 Precautionary Measures: Applying the Health Belief Model and Generalised Social Beliefs to a Probability Community Sample. Issue 4 (3rd October 2020) - Tong, Kwok Kit; Chen, Juliet Honglei; Yu, Eilo Wing‐yat; Wu, Anise M. S.
Abstract : Background: In the face of the global pandemic of coronavirus disease‐2019 (COVID‐19), people's adherence to precautionary behavioral measures (e.g. social distancing) largely influences the effectiveness of those measures in containing the spread of the coronavirus. The present study aims at testing the applicability of the health belief model (HBM) and generalised social beliefs (i.e. social axioms) to explore strategies for promoting adherence to COVID‐19 precautionary measures. Methods: We conducted a telephone survey with a two‐step stratified random sampling method and obtained a probability sample of 616 adults in Macao, China (18–87 years old; 60.9% women) in April 2020. Results: Our participants showed stronger adherence to some COVID‐19 precautionary measures (e.g. face mask wearing; 96.4%) but not others (e.g. social distancing; 42.3%). Their adherence to those measures was found to be significantly associated with four HBM factors and two social axioms, after controlling for gender, age, and years of education. Conclusions: The HBM and the generalised social beliefs of social cynicism and reward for application can be applied to understanding adherence to precautionary measures against COVID‐19. Strategies based on beliefs were proposed to facilitate the promotion of precautionary measures.